Unraveling the Interplay among Inflation, Rice Prices, and Farmers Terms of Trade in Central Java, Indonesia - Setiawan, Avi Budi; Yusuf, Mochammad; Prajanti, Sucihatiningsih Dian Wisika; Prasetyo, Farhan Hadi; Bowo, Prasetyo Ari; Maftukhah, Ida (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2024)
Farmers' Terms of Trade is an essential variable for measuring welfare and is also affected by other factors, such as inflation and rice prices. Therefore, this study aimed to investigate the interplay among inflation, rice prices, and farmers' Terms of Trade in food crop farming in Central Java Province, in short and long term using a dynamic model. A quantitative method employing Autoregressive distributed lags (ARDL) model was used with monthly data from January 2018 to March 2023. The results showed that rice prices and inflation partially had a significant and positive influence on farmers’ Terms of Trade in long term. According to short term estimation, the dependent variable was significantly and positively influenced by farmers' Terms of Trade from the previous 1-2 months. Inflation rate was also shown to have a positive influence on the variable in short term. In addition, rice prices had a positive and significant impact in the previous 3 months, but had no significant influence in recent months. Based on the results, inflation could positively influence farmers’ Terms of Trade in short and long term. However, the recent rice prices had no impact due to the requirement of time lags. The assessment findings showed that recent rice prices could significantly increase farmers’ Terms of Trade in the next 3 months and long term period.